The Irish exclusionary rule after DPP v JC. (December 2015) - Leon, Clare; Ward, Tony
Abstract : This commentary updates the paper 'Excluding evidence (or staying proceedings) to vindicate rights in Irish and English law' by analysing the recent decision of the Supreme Court of Ireland in DPP v JC . It argues that although the court has relaxed the exclusionary rule in one major respect, it has strengthened it in others, and that Ireland's approach to unconstitutionally or illegally obtained evidence remains very different from that of England and Wales.